2019
DOI: 10.18332/tpc/113355
|View full text |Cite
|
Sign up to set email alerts
|

Does adding a psychosocial cessation intervention to an existing life-skills and tobacco-prevention program influence the use of tobacco and supari among secondary school students?: Findings from a quasi-experimental trial in Mumbai, India

Abstract: INTRODUCTION This study aimed to test whether school-going adolescents who self-report tobacco and/or supari use are more likely to quit if a school-based psychosocial cessation intervention is added to an existing life-skills and tobaccoprevention program. METHODS A quasi-experimental trial with pre-test and post-test 20 weeks after the intervention was conducted with students from low-income families in 12 schools in Mumbai; six schools were randomly assigned to the intervention and the remaining to the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…It is therefore important to explore triggers and obstacles and plan ways to overcome them by developing skills such as assertion, decisionmaking, conflict management and so forth. This view was consistent with Chatterjee et al (2019) who asserts that identifying what may cause cravings and relapse is important as each person has different individual, environmental and emotional influencing factors. Understanding what may trigger cravings and relapse allows adolescents to manage and prevent it.…”
Section: Programme Outcome Considerations (Prongs)supporting
confidence: 84%
“…It is therefore important to explore triggers and obstacles and plan ways to overcome them by developing skills such as assertion, decisionmaking, conflict management and so forth. This view was consistent with Chatterjee et al (2019) who asserts that identifying what may cause cravings and relapse is important as each person has different individual, environmental and emotional influencing factors. Understanding what may trigger cravings and relapse allows adolescents to manage and prevent it.…”
Section: Programme Outcome Considerations (Prongs)supporting
confidence: 84%
“…In another study using the LifeFirst program, a 20-week pre- and post-test quasi-experimental trial was conducted on school-going adolescents from 12 schools in Mumbai. 32 The school-based psychosocial cessation intervention program had six group sessions consisting of counseling to address barriers to quit and ways to overcome them. This intervention was added to an already existing life skills and tobacco prevention program (the components of which were awareness of harms, refusal skills, and becoming advocates for change).…”
Section: Resultsmentioning
confidence: 99%
“…One study also evaluated the feasibility of providing psychological intervention. 26 Two Indian studies 31,32 developed a school-based psychosocial cessation intervention plan to reduce AN intake among school children. Most studies demonstrated an increase in awareness related to the harms of AN, motivation to quit, and a reduction in AN use.…”
Section: Discussionmentioning
confidence: 99%
“…In our review, there were nine cluster RCTs. [ 19 , 20 , 21 , 25 , 26 , 27 , 30 , 32 , 33 ] The number of clusters varied from 11 to 60. [ 25 , 33 ] Among these, four RCTs used geographical units such as low-income administrative blocks, community development blocks, villages and polling areas as clusters.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 , 25 , 27 , 33 ] Three studies used schools as clusters. [ 20 , 26 , 30 ] Other study settings were manufacturing worksite units and designated microscopy centres. [ 21 , 32 ]…”
Section: Resultsmentioning
confidence: 99%